Effectiveness of Zakat and Benevolent Fund Distribution: Evidence from Bank Syariah Indonesia (2021–2023) - Alfi Khilmi Khusnia; Inna Putri Istiqomah; Syana Sekar Izaty (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This study aims to analyze the effectiveness of zakat and benevolent fund distribution at Bank Syariah Indonesia during the 2021–2023 period. As an Islamic financial institution, the bank performs not only commercial intermediation functions but also social responsibilities through the management of zakat, infaq, sadaqah, and non-halal funds. The effectiveness of fund distribution is an important indicator in assessing the optimization of Islamic banking’s social role. This research employs a descriptive quantitative approach using secondary data obtained from the annual reports of Bank Syariah Indonesia. The Allocation to Collection Ratio (ACR) is applied to measure effectiveness by comparing the amount of funds distributed with the total available funds (collection plus beginning balance). The results show that zakat fund distribution falls into the moderately effective category, with a declining trend from 55% in 2021 to 51% in 2023. In contrast, benevolent funds demonstrate higher effectiveness, reaching the highly effective category in 2022 with a ratio of 93%. These findings indicate differences in fund management mechanisms and distribution priorities. The study suggests the need to optimize zakat fund allocation to minimize idle balances and enhance social impact.